Efeito da adição de nanocelulose fibrilada nas propriedades do estado fresco de pastas cimentícias - Bilcati, Géssica Katalyne; Lima, Bruna Régio de; Holzmann, Henrique Ajuz; Lengowski, Elaine Cristina; Langaro, Eloise Aparecida (Ambiente Construído, 2026)
Portland cement is widely used in civil construction due to its high compressive strength, durability, and ease of production. However, it has limitations in terms of sustainability. Nanocellulose, a material derived from biomass, emerges as a sustainable alternative with the potential to enhance the properties of cementitious composites and reduce their environmental impact. The present study aimed to investigate the behavior of fresh-state cement pastes produced with different concentrations of fibrillated nanocellulose (NFC) pulp (1.0%, 1.5%, 2.0%, and 2.5%). The consistency index was evaluated through the flow table test, along with bulk density, incorporated air content, and rheological behavior via the squeeze-flow test. The results obtained from the flow table test indicated that the addition of NFC pulp influenced the fluidity of the cement pastes, promoting greater spread, especially at higher concentrations. The addition of fibrillated nanocellulose pulp in the 1.0% and 1.5% formulations resulted in a decrease in bulk density and an increase in incorporated air content when compared to cement pastes without NFC. However, these changes were not statistically significant at the 95% confidence level. The squeeze-flow test showed that the fibrillated nanocellulose pulp contributed to improved plasticity of the cement pastes.